TRADITIONAL RURAL WETLANDS IN HARYANA STATE OF INDIA ARE CURRENTLY CONFRONTING MULTICORNERED THREATS LEADING TO EXTINCTION SOONER THAN LATER - Dr.Rohtash chand Gupta; Dr. Tirshem Kumar Kaushik (Journal of Tropical Life Science, 2012)
The most serious threat to traditional rural ponds in Haryana is associated with transformed societal behavioural patterns, ethics, values and life style, amongst several others. The siltation of ponds with adjoining areas, soil coming in with rain water is a very serious cause of stratification of rural ponds. Also contracting of village community land for sun drying of cow dung cakes inspires villagers to overload periphery of each pond with cow dung turning the premises into grave-yard of dung. This dung is the major source of polluting pond water into blackish water with high load of organic matter. Moreover, it leads to over excessive eutrophication. Building of major highways and connectivity roads have resulted into compartmentalization and degradation of village ponds. Inhabitation of peripheral village ponds boundaries by lower section of society for dwelling purposes is more threat to wetlands. The indifferent inclination of villagers towards silted ponds drenched in bad odour and blackish sludge is the story of 80% of the cases. The total blockage of run-off rainy water towards the natural age old rural ponds due to obstruction by way of human inhabitation has resulted into desertification of shallow water sheet in 90% of the cases. The oblivion of harvesting dried silt in summer for brick making has spelled doom for the ponds turning them into flat ground through successive decades and so on. The water quality in all ponds was overshooting the decaying stage due to the continuous mixing of cow dung drenched rainy water. Over excessive usage of ponds for bathing of cattle, dumping of cow dung and rotten vegetables waste has turned ponds into live sinks of dirt, garbage and rural dairy wastes. Majority of village ponds are now out of existence or in deep black sludge laden or converted into Fish-Farming wetlands. The present studies have indicated that Winter migratory birds like Greylag Goose Anser anser, Bar-headed Goose Anser indicus, Mallard Anas platyrhynchos, Gadwall Anas strepera, Northern Shoveller Anas clypeata, Northern Pintail Anas acuta, Garganey Anas querquedula, Common Teal Anas crecca, Common Pochard Aythya ferina, Tufted Pochard Aythya fuligula, Common Coot Fulica atra, Little Ringed Plover Charadrius dubius, Kentish Plover Charadrius alexandrines, Spotted Redshank Tringa erythropus, Common Redshank Tringa tetanus, Marsh Sandpiper Tringa stagnatilis, Wood Sandpiper Tringa glareola and Pied Avocet Recurivirostra avosetta arrive in the extremely dilapidated rural ponds in Haryana from far off places including Russia, Siberia, China, and Caspian region, east Asia each winter season without any break. As such the extinction of ponds in Haryana directly threatens global avian biodiversity. Keywords: Traditional Rural Wetlands, Perennial Rainy Water, Road Side Puddles, Land Filling, Commercial and Residential Construction, Highway reconstruction